Understanding Phase Contrast MR Angiography A Practical Approach with MATLAB examples - Suresh Paul, Joseph; Subha GR.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Providing many unique MATLAB codes and functions throughout, this book covers the basics of Magnetic Resonance Imaging (MRI), leading to an in-depth understanding of the concepts and tools required for analysis and interpretation of Phase Contrast MR Angiography (PC-MRA). The concept of PC-MRA is often difficult, but essential for practicing engineers and scientists working in MR related areas. The concepts are better understood by uniquely combining the physical principles of fluid flow and MR imaging, laid out by modeling the theory and applications using a commonly used software tool MATLAB®. The book starts with a detailed theory of PC-MRA followed by a description of various image processing methods, including detailed MATLAB codes used for their implementation. The flow concepts in the context of MR imaging are explained using MATLAB based simulations.
Keywords: Biomedical engineering; Medical physics; Cardiology; Biomedical Engineering and Bioengineering; Medical Physics; Cardiology